CHARACTER EDUCATION IN TERE-LIYE’S AYAHKU (BUKAN) PEMBOHONG - Safrizal Safrizal; Purwarno Purwarno; Andang Suhendi (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2019)
This research aims at describing the character education in the novel Ayahku (Bukan) Pembohong by Tere Liye. The character education in this novel was analysed using the theory proposed by Zamroni (2011). The focus of the research is the character values reflected by the characters of the novel. It is reflected that the understanding of life is not as complicated as people think if people always thank God for whatever God has been bestowed on them. Life is a grace of God that must be thanked. The method of research applied is qualitative descriptive. The researc result shows that the character educations reflected in the novel are honesty, discipline, hardworking, and friendly. Tere Liye’s novel was full of tangible behaviours performed by the main characters to handle the events in various forms of interaction among the characters.